Genomic Variability and Post-translational Protein Processing Enhance the Immune Evasion of Mycoplasma hyopneumoniae and Its Interaction With the Porcine Immune System - Li, Gaojian; Obeng, Enoch; Shu, Jinqi; Shu, Jianhong; Chen, Jian; Wu, Yuehong; He, Yulong (Frontiers in Immunology, 2020)
Mycoplasma hyopneumoniae (M. hyopneumoniae, Mhp) is a geographically-widespread and economically-devastating pathogen that colonises ciliated epithelium, the infection of Mhp damnifys the mucociliary function as well as leading to Mycoplsama pneumonia of swine (MPS). MPS is a chronic respiratory infectious disease with high infectivity, and the mortality can be increased by secondary infections as the host immunity gets down-regulated during Mhp infection. The host immune response is regarded as the main driving force for the disease development, while MPS is prone to attack repeatedly in farms even with vaccination or other treatments. As one of the smallest microorganisms with limited genome scale and metabolic pathways, Mhp can use several mechanisms to achieve immune evasion effect and derive enough nutrients from its host, indicating that there is a strong interaction between Mhp and porcine organism. In this paper, we summarized the immune evasion mechanisms from genomic variability and post-translational protein processing. Besides, Mhp can induce the immune cells apoptosis by ROS production, excessive NO and caspase activation, and stimulate the release of cytokines to regulate inflammation. This paper seeks to provide some new points to reveal the complicated interaction between microorganisms and the immune system with Mhp as a typical example, further providing some new strategies for the vaccines development against Mhp infection.